2010
DOI: 10.1589/jpts.22.217
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of MAPK Isoforms during Cast-Immobilization -Induced Atrophy in Rat Gastrocnemius Muscle

Abstract: Abstract.[Purpose] The aim of the present study was to determine whether the expression of mitogenactivated protein kinase (MAPK) isoforms is related to cast-immobilization-induced atrophy in rat skeletal muscles.[Subjects] The subjects were 24 male Sprague-Dawley rats aged 7 weeks old.[Methods] The rats were randomly divided into a control group (n=4) and four experimental groups (n=20). The experimental groups were submitted to 3, 7, 14, or 21 days of cast-immobilization to provoke disuse atrophy.[Results] T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Mitogen-activated protein kinases, such as extracellular signal-regulated kinase 1/2, stress-activated protein kinase/ c-Jun NH 2 -terminal kinase, and p38 mitogen-activated protein kinase, are simultaneously involved in muscle atrophy induced by immobilization and cell starvation12, 13 ) . Furthermore, in another study, we demonstrated that cast immobilization increases the expression of myoglobin in rat gastrocnemius muscles15 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinases, such as extracellular signal-regulated kinase 1/2, stress-activated protein kinase/ c-Jun NH 2 -terminal kinase, and p38 mitogen-activated protein kinase, are simultaneously involved in muscle atrophy induced by immobilization and cell starvation12, 13 ) . Furthermore, in another study, we demonstrated that cast immobilization increases the expression of myoglobin in rat gastrocnemius muscles15 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of muscle mass and of muscle function are important for healthy life, and is important in the rehabilitation of musculoskeletal disease in the field of physical therapy 1 , 7 , 13 , 14 ) . The maintenance mechanisms of muscle mass include anabolic and catabolic signal transductions via PKB/Akt, a protein with a critical role 1 , 5 , 10 , 11 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The homogenate was centrifuged and the supernatant was collected. Proteins, 30–45 μg/lane, were separated on 12% polyacrylamide sodium dodecylsulfate gels and then transferred electrophoretically to a polyvinylidene fluoride membrane (Millipore; Bedford, MA, USA) 1 ) . Anti-PKB/Akt antibody was purchased from Santa Cruz (Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations